CORRELATION BETWEEN PLATELET TO LYMPHOCYTE RATIO AND CORONARY ARTERY NARROWING - Marziah, Enny; Ketaren, Andre Pasha; Aman, Adi Koesoema (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Coronary Heart Disease (CHD) is one of the most common diseases of the cardiovascular system, characterized by atherosclerotic lesions. Atherosclerotic vascular processes are multifactorial. One of the factors is the process of inflammation. Platelet to Lymphocyte Ratio (PLR) is a marker that predicts the atherosclerotic coronary burden. The purpose of this research was to determine the correlation between platelet to lymphocyte ratio and coronary artery narrowing in CHD patients. This research was an analytical observation with a cross-sectional design, conducted on 54 patients with CHD who underwent angiography at the Adam Malik Hospital, Medan in February–October 2016. We examined platelet count, absolute lymphocyte count and percentage of coronary artery narrowing and coronary artery narrowing in CHD patients. There is a weak correlation between platelet to lymphocyte ratio and coronary artery narrowing in CHD patients ((r=0.276)). The result of the statistic test showed no significant correlation of platelet to lymphocyte ratio and coronary artery narrowing patients (p=0.043). In this study there is a weak correlation between platelet to lymphocyte ratio and coronary artery narrowing in CHD patients.